Primary Fallopian Tube Clear Cell Adenocarcinoma in Pregnancy: Case Presentation and Review of the Literature - Mohammed Malak; Stephanie Klam (Case Reports in Obstetrics and Gynecology)
Primary fallopian tube cancer in pregnancy is rare and is even more so for the clear cell variant. Our case is the third case of primary fallopian tube cancer in pregnancy and the first case of clear cell adenocarcinoma of the fallopian tube in pregnancy. The patient presented with increasing pelvic pain starting in the second trimester. Serial ultrasound evaluations were performed and revealed a rapidly growing complex adnexal mass adjacent to the uterus. Her pregnancy was further complicated by spontaneous preterm labor and she delivered prematurely per vaginam at 31 weeks. She underwent an urgent laparotomy in the immediate postpartum period for acute aggravation of her right pelvic pain and fever. The diagnosis of tubal clear cell adenocarcinoma was subsequently made on histopathology examination.